Kyoto and the Carbon Footprint of Nations - Rahel Aichele; Gabriel Felbermayr (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
A countrys carbon footprint refers to the CO2 emissions caused by domestic absorptionactivities. Trade in goods drives a wedge between the footprint and local emissions. Weprovide a panel database on carbon footprints and carbon net trade. Using a differencesin-differences IV estimation strategy, we evaluate the Kyoto Protocols effects on carbonfootprints and emissions. Instrumenting countries Kyoto commitment by their participationin the International Criminal Court, we show that Kyoto reduced domestic emissionsin committed countries by 7%, has not lowered footprints, but increased the share ofimported over domestic emissions by 17 percentage points. This indicates carbon leakage.
Keywords: F18; F53; Q54; Q58; 330; Carbon content of trade; carbon footprint; carbon leakage; evaluation model; instrumental variables; Klimaschutz; Umweltabkommen; Außenwirtschaft; Kohlendioxid; Luftverunreinigung; Internationale Gerichtsbarkeit; Mitgliedschaft; Welt